2005
DOI: 10.1088/0029-5515/45/12/022
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for electromagnetic fluid drift turbulence controlling the edge plasma state in the Alcator C-Mod tokamak

Abstract: Plasma profiles across the separatrix and scrape-off layer (SOL) in Alcator C-Mod are examined for a range of plasma densities, currents and magnetic fields in ohmic L-mode discharges and for a subset of conditions in ohmic H-mode discharges. In all plasmas, electron pressure gradient scale lengths (Lp e) exhibit a minimum value just outside the separatrix (i.e., in the near SOL), forming the base of a weak (strong) pedestal in L-mode (H-mode) plasmas. Over a wide range of conditions in ohmic L-mode discharges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
127
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(156 citation statements)
references
References 75 publications
(197 reference statements)
28
127
1
Order By: Relevance
“…If the measured velocities were simply interpreted as E × B drifts, E r would have to change sign in less than the 3.7mm spot size, and attain its maximal values. This is in disagreement with both previous probe results [13] and measurements of the radial electric field by charge-exchange recombination spectroscopy [23]. Interpretation of the edge propagation velocity solely as v E in these regimes also contradicts the existence of the E rwell found in ref.…”
Section: A L-modecontrasting
confidence: 91%
See 1 more Smart Citation
“…If the measured velocities were simply interpreted as E × B drifts, E r would have to change sign in less than the 3.7mm spot size, and attain its maximal values. This is in disagreement with both previous probe results [13] and measurements of the radial electric field by charge-exchange recombination spectroscopy [23]. Interpretation of the edge propagation velocity solely as v E in these regimes also contradicts the existence of the E rwell found in ref.…”
Section: A L-modecontrasting
confidence: 91%
“…Nevertheless, recent experiments on Alcator C-Mod [13] have revealed a number of connections between global operating parameters (density and temperature profiles, plasma currents) and dimensionless scaling parameters of electromagnetic turbulence. These advances, together with the above transport phenomenology have led to the hypothesis that edge transport physics is described as a system near marginal stability [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…figure 4) is different respect to what has been observed for diverted L-mode discharges in C-Mod. In this configuration, LaBombard et al [29,30] found that the relevant dimensionless parameters are α d and α. It is conjectured that a different saturation mechanism could be at play in diverted shots.…”
Section: Discussionmentioning
confidence: 94%
“…Examination of probe data taken approximately 2 mm outside the LCFS has provided evidence for electromagnetic fluid drift turbulence [31] [32] setting the plasma transport state at this location. The study demonstrated experimentally both a local minimum in the pressure gradient scale length L nT = |nT /∇(nT )| and a functional dependence of normalized pressure gradient α MHD = 2µ 0 q 2 Rp /B 2 on a diamagnetic parameter α d , which is an inverse collisionality reflecting the ratio of diamagnetic drift to resistive ballooning times [33] [34].…”
Section: A Pressure Gradientmentioning
confidence: 99%